State of the art in automated map generalization - Šuba, Radan (A+BE | Architecture and the Built Environment, 2018)
Automated map generalization is a difficult, complex and computational very intensive problem. The aim of this chapter is to study existing solutions and state of the art. It also provides context and motivation for why we tackle this problem by applying varioscale approach. In Section 2.1, the paradigm shift in map generalization in a digital environment is studied. We investigate if requirements in the map making process have changed with the transformation from paper to digital environment and if so what are the consequences. Then Section 2.2 investigates how National Mapping Agencies are dealing with automated generalization process in general and what are their recent developments. In Section 2.3, the focus is on the issue of continuous map generalization, which is becoming more researched as an alternative to the map generalization for discrete predefined scales. Section 2.4 demonstrates another problem of digital map environment where the number of map scales available is not sufficient for user interactions. Final remarks are covered in 2.5.